Race and national security - Sirleaf, Matiangai (Just security, 2023)
"The Race and National Security volume interrogates what it would mean for the field and concept of national security to take issues of race and racial justice seriously. This book seeks to fundamentally shift how national security is conceptualized by helping to redefine the field and practice. This volume clarifies how white supremacy informs and shapes the parameters of what "counts" as national security. The sheer breadth and depth of the topics and vantage points covered challenge conventional knowledge about national security. Contributions in this volume refocus the frame of reference to center race and historically subordinated groups. Through this reframing and focusing on the faces at the bottom of the well, the contributions in this volume create a far more accurate understanding of how race manifests in national security domestically, transnationally, and globally. This volume is ground-breaking as numerous interventions in this book explicitly engage with the period of national and global reckoning on race and transformation, and the ongoing backlash in ways that other projects have not. This book explicitly considers what it would mean to subvert White hegemonic power and dominance in national security. It recognizes not only the gravity of the historical moment that continues to unfold in the United States and elsewhere, but also the opening and potential that it presents to spark and revitalize debate and policy changes on these crucial issues globally. This volume serves as a catalyst for remembering, exposing, and reimagining the role of race in national security"--